Discrepancies in sleep diary and actigraphy assessments in adults with fibromyalgia: Associations with opioid dose and age. (31st July 2018) - Curtis, Ashley F.; Miller, Mary Beth; Boissoneault, Jeff; Robinson, Michael; Staud, Roland; Berry, Richard B.; McCrae, Christina S.
Abstract: Sleep diary and actigraphy assessments of insomnia symptoms in patients with fibromyalgia (FM) are often discrepant. We examined whether opioid dose and age interact in predicting magnitude or direction of discrepancies. Participants ( N = 199, M = 51.5 years, SD = 11.7) with FM and insomnia completed 14 days of diaries and actigraphy. Multiple regressions determined whether average opioid dose and its interaction with age predicted magnitude or direction of diary/actigraphy discrepancies in sleep onset latency (SOL), wake after sleep onset (WASO) and sleep efficiency (SE), controlling for sex, use of sleep medication, evening pain and total sleep time. Higher opioid dose predicted greater magnitude of discrepancy in SOL and SE. Opioid dose interacted with age to predict direction but not magnitude of discrepancy in SOL and SE. Specifically, higher opioid use was associated with better subjective (shorter SOL, higher SE) than objective reports of sleep among younger adults, and longer subjective than objectively measured SOL among older adults. Opioid dose did not predict magnitude or direction of WASO discrepancies. In FM, a higher opioid dose increases diary/actigraphy SOL and SE discrepancies, and direction of discrepancies may depend on age. We speculate that increased opioid use combined with age‐related factors, such as slow wave sleep disruption, increased awakenings and/or cognitive decline, may impact perceived sleep.